ENRICHING STUDENTS’ VOCABULARY MASTERY USING GRAPHIC ORGANIZERS - Darmawan, Syaifudin Latif (Universitas Muhammadiyah Metro, 2017)
This action research is carried out to (1) identify whether graphic organizers enrich student’s vocabulary mastery; and (2) to describe the classroom situation when graphic organizers are employed in instructional process of vocabulary. The research is conducted in two cycles from March to May 2016/2017 in the eight years of SMP Muhammadiyah Sekampung, East lampung. The procedure of the research consists of identifying the problem, planning the action, implementing the action, observing the action, and reflecting the result of the research. Qualitative data are collected through interviews, observations, questionnaires, and research diaries. Quantitative data are collected through tests. To analyze qualitative data, the researcher used constant comparative method. It consists of four steps: (1) comparing incidents applicable to each category; (2) Integrating categories and their properties; (3) delimiting the theory; (4) Writing the theory. Meanwhile, to analyze quantitative data, the researcher employed descriptive statistics. The result of the research shows that using graphic organizers can enrich students’ vocabulary mastery and classroom situation. The improvement on students’ vocabulary included; a) the students are able to speak English; b) the students are able to understand the meaning of the text as they have a lot of vocabularies. The improvement of the classroom situation; (a) students come on time in the class (b) students are more motivated to join the class (c) Students pay more attention in the instructional process (d) students’ participation in responding the questions are high.